COVID-19 Response Efficacy with Biofarma's Cold Chain Vaccine Distribution System in Indonesia: An Analysis of Technology and Policy Synergy - Nugrahanto, Ardhy (Green Publisher Indonesia, 2023)
This study delves into the synergy between technology and policy in Biofarma's Cold Chain Vaccine Distribution System in Indonesia amid the pandemic. This research aims to identify and quantify the tangible and intangible benefits of technology-policy integration, assess the system's influence on the timeliness and quantity of vaccine delivery, and evaluate the maintenance of vaccine quality across Indonesia's diverse regions. Utilizing a qualitative methodology, the study conducted extensive interviews with three representatives from different Indonesian provinces to uncover the impacts of technology and policy integration on vaccine distribution. The results spotlight several key patterns those are 1) Technological Backbone: Data Integration & Distribution: Automation has significantly transformed coordination and precision in vaccine distribution. 2) Operational Revolution: Efficiency & Adaptability: The system has notably enhanced operational efficiency and adaptability. 3) Regional Nuances: System Challenges & Refinements: Identifying unique challenges across various regions shed light on factors impacting the efficacy of the distribution system. 4) Vaccine Safeguarding: Real-time Monitoring & Inventory Transparency: Real-time monitoring and transparent inventory management ensure vaccine quality and reliability. 5)Horizon Scanning: Technological Advancements & Environmental Adaptations: Recommendations for technological advancements and proactive measures to refine vaccine distribution strategies have emerged. Refined and named patterns accurately represent the essence of the data, emphasizing the pivotal role of technology and policy integration in effective vaccine distribution amid the COVID-19 crisis. The study underscores the critical alignment of technology and policy to confront challenges and enhance vaccine distribution, impacting the ongoing response to COVID-19 and future global humanitarian operations.